The Implementation of Electronic Portfolio Assessment in Learning Chemistry through Google Classroom to Increase Students’ Critical Thinking Skills - Nuryanto Nuryanto; Nahadi Nahadi; Galuh Yuliani (AL-ISHLAH: Jurnal Pendidikan, 2024)
Assessment is crucial in evaluating the success of learning and student competencies. Among the essential 21st-century skills is critical thinking. Furthermore, technological advancements necessitate the integration of digital media in education, including assessment processes. One such digital assessment method is the electronic portfolio assessment using Google Classroom. This study aimed to examine the implementation of electronic portfolio assessment via Google Classroom to enhance students' critical thinking skills. The research employed a literature review approach, drawing data from books and online journals. Data collection involved gathering information from several books and online journals pertinent to the research topic. Primary data sources included articles published in national and international journals from 2012 to 2023. Content analysis was used to analyze the data. The study's findings indicate that electronic portfolio assessment, coupled with feedback, can enhance students' critical thinking skills. Additionally, the features integrated into Google Classroom can further stimulate students' critical thinking during the learning process. Therefore, it can be concluded that electronic portfolio assessment through Google Classroom effectively enhances students' critical thinking skills.